Validity of the Rasch Model-Based Mathematical Critical Thinking Ability Instrument - Mawaddah, Dinda Aulia; Faradillah, Ayu; Alyani, Fitri (Pattimura Proceeding, 2024)
Critical intellectual skills are very necessary to make a decision, but students' critical intellectual abilities are still very low due to students' lack of ability to solve problems. This research aims to determine the results of instrument validation of applications of the Rasch model to critical thinking abilities. This study employs survey methodologies together with a quantitative methodology. The subjects of this research consisted of 134 high school students consisting of class XI. The results of this study showed two valid items, with one misfit item and five misfit items, while the DIF test showed all items indicated DIF. Testing the reliability of the instrument with the Winsteps application, obtained reliability with a Cronbach Alpha (KR-20) of 0.87, it appears that 0.87 is greater than 0.7 thisfalls into the category of excellent. People's 0.84 dependability score falls into the excellent range. An item's dependability of 0.98 falls within the excellent range. The 2.31person separation falls within the "good" category.